Mind, brain and technology : learning in the age of emerging technologies - Parsons, Thomas D.; Lin, Lin (Professor of learning technologies); Cockerham, Deborah (Cham, Switzerland : Springer, 2019)
"As technology becomes increasingly integrated into our society, cultural expectations and needs are changing. Social understanding, family roles, organizational skills, and daily activities are all adapting to the demands of ever-present technology, causing changes in human brain, emotions, and behaviors. An understanding of the impact of technology upon our lives is essential if we are to adequately educate children for the future and plan for meaningful learning environments for them. Mind, Brain and Technology provides an overview of these changes from a wide variety of perspectives. Designed as a textbook for students in the fields and interdisciplinary areas of psychology, neuroscience, technology, computer science, and education, the book offers insights for researchers, professionals, educators, and anyone interested in learning more about the integration of mind, brain and technology in their lives. The book skillfully guides readers to explore alternatives, generate new ideas, and develop constructive plans both for their own lives and for future educational needs." -- Publisher's description
Part I. Introduction: Mind, Brain, and Learning Technologies. -- Rethinking Learning in the Rapid Developments of Neuroscience, Learning Technologies, and Learning Sciences / Lin Lin, Thomas D. Parsons, and Deborah Cockerham -- Complexity, Inquiry Critical Thinking, and Technology: A Holistic and Developmental Approach / Jonathan Michael Spector -- Educational Neuroscience: Exploring Cognitive Processes that Underlie Learning / Pavlo D. Antonenko -- Part II. Educational Technologies for Assessment and Training. -- Close Relationships and Virtual Reality / Sabrina A. Huang and Jeremy Bailenson -- Uses of Physiological Monitoring in Intelligent Learning Environments: A Review of Research, Evidence, and Technologies / H Chad Lane and Sidney K. D'Mello -- Gaze-Based Attention-Aware Cyberlearning Technologies / Sidney K. D'Mello -- Using Motion Capture Technologies to Provide Advanced Feedback and Scaffolds for Learning / Andreja Istenic Starcic, William Mark Lipsmeyer, and Lin Lin -- Virtual School Environments for Neuropsychological Assessment and Training / Thomas D. Parson, Tyler Duffield, Timothy McMahan, and Unai Diaz-Orueta -- Part III. Policies and Praxes. -- Implications of Social Neuroscience for Learning Technology Research and Development / Nancy W.Y. Law and Haley W.C. Tsang -- Cross-Sectional Studies Investigating the Impacts of Background Sounds on Cognitive Task Performance / Deborah Cockerham, Lin Lin, Zhengsi Chang, and Mike Schellen -- Neuroethics in Educational Technology: Keeping the Brain in Mind When Developing Frameworks for Ethical Decision-Making / Thomas D. Parsons.
Includes bibliographical references and indexes.
Keywords: Educational technology; Computer-assisted instruction; Technology -- Social aspects